Resin transfer moulding: Novel fabrics and tow placement techniques in highly loaded carbon fibre composite aircraft spars - Mills, Andrew; Patel, Zahir; Dell'Anno, Giuseppe; Frost, Matthew (SAMPE - Society for the Advancement of Material and Process Engineering, 2007)
A BAE Systems /UK EPSRC funded project Flaviir, is investigating the design and manufacture of low cost carbon fibre composite airframe structures. Novel binder coated unidirectional fibre tapes and tows were developed to enable the design of optimised primary structures. The RTM technique was applied to mould net shape sections of spar components. Various designs of wing attachment lugs were manufactured with a range of reinforcement materials, including non crimp fabric, novel binder coated tapes and conventional unidirectional prepreg. Alongside these, a novel technique termed optimised tow lay up (OTL) was used to reduce the weight. Binder coated carbon fibre tow is placed around the structure in the principal stress directions to increase both bearing strength and overall component stiffness. The novel materials, manufacturing technique and initial element test results are presented.